Self Acceptance Atribution in the Context of Personality Acceptance - Нoshovska D.; Hoshowskyі Ya. (Psychological Prospects Journal, 2013)
Speech goes in the article about the psychological structure of acceptance as base formation of personality acceptance. Essence components and specific of self acceptance atribution of personality are exposed on the juvenile stage of ontogenesis. Acceptance as a general positive setting on itself is determined as a major personality motivational aspect of consciousness.